Acid rain research : do we have enough answers? : proceedings of a speciality conference, 's-Hertogenbosch, the Netherlands, 10-12 October 1994 - Heij, G.; Erisman, J. W. (Jan Willem) (Studies in environmental science, 1995)
Representing the Proceedings of the International Speciality Conference "Acid Rain Research; Do we have enough answers?", this book provides a valuable conclusion to the coordinated research on acidification in the Netherlands from 1985 to 1994. The book focuses on atmospheric deposition, effects of acid deposition on forest ecosystems in the Netherlands, and future acidification research. Special attention is given to: trace gases; ammonia; and particle deposition; and the overall assessment of deposition loads to ecosystems and soils is also discussed. This volume will be invaluable to environmental scientists, ecologists, and those involved in atmospheric science/pollution.